Analisa Pengaruh Efek P – ∆ Terhadap Kinerja Struktur Bangunan Bertingkat Pada Daerah Rawan Gempa - Rahmadi Valdis; Sapta Sapta; Amelia Rajela (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
High-rise buildings are highly vulnerable to the effects of lateral loads, particularly seismic loads. One important phenomenon that must be considered in structural design is the P-Δ (P–delta) effect. This effect occurs due to the interaction between axial forces in structural elements and the lateral displacement of the building, which generates additional moments. These additional moments can increase structural deformation and reduce overall stability. In multi-story buildings, especially those with more than 10 floors, the influence of the P-Δ effect becomes more significant because of the large axial forces in the columns combined with relatively high lateral displacements. This study aims to analyze the influence of the P-Δ effect on the behavior of high-rise building structures using numerical analysis based on the seismic design standards applied in Indonesia. The scope of the study focuses on modeling multi-story building structures with the aid of structural analysis software, with variations in the number of floors, to determine the extent of the P-Δ effect on lateral displacement, internal moments, and structural safety factors. The results of the analysis are expected to provide a deeper understanding of the significant role of the P-Δ effect in seismic-resistant building design. These findings are also intended to serve as a reference for designers and civil engineering practitioners in ensuring that high-rise building designs remain safe, stable, and compliant with applicable regulations.